The contribution of two common shrub species to aboveground and belowground carbon stock in Iberian dehesas (Journal of Arid Environments, 2013)
Shrubs play an important role in water-limited agro-silvo-pastoral systems by providing shelter and forage for livestock, for erosion control, to maintain biodiversity, diversifying the landscape, and above all, facilitating the regeneration of trees. Furthermore, the carbon sink capacity of shrubs could also help to mitigate the effects of climate change since they constitute a high proportion of total plant biomass. The contribution of two common extensive native shrub species (Cistus ladanifer L. and Retama sphaerocarpa (L.) Boiss.) to the carbon pool of Iberian dehesas (Mediterranean agro-silvo-pastoral systems) is analyzed through biomass models developed at both individual (biovolume depending) and community level (height and cover depending). The total amount of carbon stored in these shrubs, including above- and belowground biomass, ranges from 1.8 to 11.2 Mg C ha 1 (mean 6.8 Mg C ha 1 ) for communities of C. ladanifer and from 2.6 to 8.6 Mg C ha 1 (mean 4.5 Mg C ha 1 ) for R. sphaerocarpa. These quantities account for over 20e30% of the total plant biomass in the system. The potential for carbon sequestration of these shrubs in the studied system ranges 0.10e1.32 Mg C ha 1 year 1 and 0.25e1.25 Mg C ha 1 year 1 for the C. ladanifer and R. sphaerocarpa communities’ respectively